Overview Of Hypertension In Adolescents - Sumarni, Sumarni; Nurhikmawati, Nurhikmawati; Faika Annisya (Sean Institute, 2024)
Hypertension in adolescents can persist into adulthood and has higher morbidity and mortality. Globally, the prevalence of hypertension in adolescents reaches around 10% and 14% experience prehypertension. The increase in hypertension in adolescents is caused by both modifiable and non-modifiable risk factors. Risk factors that cannot be modified include family history of disease, namely hypertension or other cardiovascular disease, genetics, premature birth, low birth weight, gender, race. Modifiable risk factors relate to obesity, dietary habits, salt intake, physical activity, smoking, poor sleep quality. The diagnosis of adolescent hypertension is different compared to adult patients, in the form of a detailed history ranging from fetal growth patterns to habitual history. Physical examination blood pressure measurements are adjusted and classified based on percentiles. Treatment starts from lifestyle changes to administering pharmacology tailored to the patient's condition.